Reconstructing the Environmental Licensing Law Based on Ecological Justice - Achmad Muchsin; I Gusti Ayu Ketut Rachmi Handayani; Sri Wartini; Ridwan Arifin (Administrative and Environtmental Law Review, 2025)
This research examines the legal implications of changing the nomenclature from “environmental permits” to “environmental approvals” in Indonesia’s environmental licensing law. Moving beyond a conventional public law focus, it highlights the role of private law instruments in advancing climate change mitigation and adaptation. The core question addressed is whether this terminological shift aligns with the principles of ecological justice and how environmental licensing law should be reconstructed to uphold these values. Using a doctrinal legal research method, the analysis integrates statutory, conceptual, and philosophical perspectives, employing techniques of interpretation and construction. The findings indicate that while certain reforms under the Job Creation Law support ecological justice, others undermine it. The research concludes that the current framework requires comprehensive reconstruction to more effectively embody ecological justice and strengthen climate action.